2006
DOI: 10.1007/s10840-006-7619-6
|View full text |Cite
|
Sign up to set email alerts
|

Coronary sinus morphology in different types of supraventricular tachycardias

Abstract: The easier CS cannulation in patients with typical AVNRT could be due to a bigger CS size and to a more windsock morphology. The CS size and morphology may be a very important substrate of tachycardia in patients with AVNRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Electrophysiological studies suggest that the perinodal area in the posteroinferior AV junction could be responsible for the multipathway phenomena or the circuit for AVNRT. Several clinical series have shown morphological differences of the posteroinferior AV junction including CS morphology in patients with and without AVNRT; the proximal CS was larger in patients with AVNRT 12–14 . One study, however, found no demonstrable correlations 15 .…”
Section: Discussionmentioning
confidence: 98%
“…Electrophysiological studies suggest that the perinodal area in the posteroinferior AV junction could be responsible for the multipathway phenomena or the circuit for AVNRT. Several clinical series have shown morphological differences of the posteroinferior AV junction including CS morphology in patients with and without AVNRT; the proximal CS was larger in patients with AVNRT 12–14 . One study, however, found no demonstrable correlations 15 .…”
Section: Discussionmentioning
confidence: 98%
“…The diameter of the coronary sinus has been shown to be significantly larger in patients with atrioventricular nodal re-entry tachycardia compared with other types of arrhythmia [9], with mean values of 15.93±4.8 mm at the ostium, to 10.79±5.11 mm at 10 mm from the ostium. Patients with arrhythmias were not included in our study group; therefore the difference in the CS diameter should not be related to the presence of the heart rhythm disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Although the analysis of CS has been performed by means of CT since the rudiments of this technique [8], detailed CT assessment of this structure is a relatively new topic. CT is currently utilised in patients with heart rhythm disturbances [9] for the planning of cardiac procedures [10,11], or in patients with persistent left SVC [12]. Changes in CS diameter measured by CT were recently reported for diagnosis of cardiac tamponade [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that CS cannulation was easier and simpler in patients with AVNRT diagnosis than in patients with other types of SVT . The CS morphology was evaluated by fluoroscopy in previous studies . The CS can be visualized by using zoom M‐mode recordings of it in apical two‐ and four‐chamber views.…”
Section: Introducti̇onmentioning
confidence: 99%